2021
DOI: 10.1093/eurheartj/ehab724.2846
|View full text |Cite
|
Sign up to set email alerts
|

TheSGLT-2 inhibitor dapagliflozin ehnanced the anticancer activities and exerts cardioprotective effects during exposure to ipilimumab through NLRP3 inflammasome and pro-fibrotic cytokines

Abstract: Background The clinical trial “DECLARE-TIMI 58” (Dapagliflozin Effect on Cardiovascular Events-Thrombolysis in Myocardial Infarction 58), demonstrated that dapagliflozin, a Sodium glucose cotransporter 2 inhibitor, reduces the composite end point of cardiovascular death/hospitalization for heart failure in a broad population of patients with type 2 diabetes mellitus. Immune checkpoint inhibitors (ICIs) have revolutionized cancer treatment, achieving unprecedented efficacy in multiple malignan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Subsequent to landmark studies demonstrating the cardioprotective effects of SGLT2 inhibitors in HF, numerous in vivo ( Table 2 ) and in vitro ( Table 3 ) studies, starting in 2019, have underscored the cardioprotective roles of SGLT2 inhibitors in mitigating cardiotoxicity induced by various cancer treatments, including DOX, 17 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 sunitinib, 20 trastuzumab, 21 cisplatin, 19 ipilmumab, 54 , 55 ponatinib, 56 and carfilzomib. 57 DOX has received particular attention because of its status as the most cardiotoxic cancer treatment and its widespread use.…”
Section: Sglt2 Inhibitors In Cardio-oncologymentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent to landmark studies demonstrating the cardioprotective effects of SGLT2 inhibitors in HF, numerous in vivo ( Table 2 ) and in vitro ( Table 3 ) studies, starting in 2019, have underscored the cardioprotective roles of SGLT2 inhibitors in mitigating cardiotoxicity induced by various cancer treatments, including DOX, 17 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 sunitinib, 20 trastuzumab, 21 cisplatin, 19 ipilmumab, 54 , 55 ponatinib, 56 and carfilzomib. 57 DOX has received particular attention because of its status as the most cardiotoxic cancer treatment and its widespread use.…”
Section: Sglt2 Inhibitors In Cardio-oncologymentioning
confidence: 99%
“… 32 Researchers have investigated several models of DOX cardiotoxicity, including acute 39 , 42 , 43 , 48 , 51 and chronic 17 , 39 , 41 , 46 , 47 , 48 cardiotoxicity, cardiorenal syndrome, 40 and conditions involving diabetic 44 and nondiabetic rodents. Empagliflozin 17 , 20 , 21 , 39 , 40 , 41 , 42 , 43 , 49 , 55 , 56 and dapagliflozin 44 , 45 , 46 , 48 , 50 , 51 , 52 , 53 , 54 , 56 have emerged as the most commonly used SGLT2 inhibitors, followed by canagliflozin. 19 , 57 Notably, no in vivo studies have reported the protective effects of canagliflozin against DOX, with only 1 in vivo study reporting the cardioprotective effects of canagliflozin against cisplatin 19 and an in vitro study demonstrating its efficacy against carfilzomib.…”
Section: Sglt2 Inhibitors In Cardio-oncologymentioning
confidence: 99%
See 2 more Smart Citations